Social comparison and peer effects at an Elite College - Goethals, George R. (2000)
A study was conducted to see whether peer effects could be observed among undergraduates at Williams College, an elite four-year liberal arts school. Specifically, the study explored whether students in the bottom third of their class, with average SAT's of about 1300, would perform better in writing about newspaper articles they read and discussed in groups of three if the two others in the group were academically superior -- from the top third of their class, with SAT's averaging about 1500 -- rather than similar -- also from the bottom third of the class. The results showed that women subjects performed better if their discussion partners were from the top third of the class, but men did better if their discussion partners were from the bottom third. Alternative analyses comparing subjects who had better or worse discussion partners as determined by the quality of their peers videotaped discussion statements, showed that across gender subjects did better written work when their discussion partners were better. The results were interpreted in terms of the principles of social comparison theory (Festinger, 1954).
Paper provided by Department of Economics, Williams College in its series Williams Project on the Economics of Higher Education with number Document Paper (DP -55).
This paper is intended for private circulation.
Includes bibliographical references.
Keywords: Social comparison; Peer review; College